(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
This study was conducted in Zawita and Atrush in Dohuk governorate in northern Iraq and on the trees of the pine (Pinus brutia Ten.) and the oak (Quercus spp.) trees growing naturally in the study site and on an area of (495.47 km2), located between two longitudes (43° 2’ 30"), (43° 25’ 0") East, and two latitudes (36° 47’ 30"), (37° 0’ 0") North, at an altitude ranging between (542 - 1603) meters, and these trees are among the naturally renewable natural resources and must Maintaining and managing them efficiently requires the preparation of primary baseline data on what exists of these resources and how they interact with each other in the ecosystem. Field data were collected from (24) circular samples with a radius of (17.9) m, and the area of one sample was (1006) m2, and field measurements included the variables of one tree, namely (geographical coordinates, diameter at breast height, crown center height, crown width). Soil samples were also taken from the centers of those samples and the necessary analyzes were conducted on them.